Emerging role of hypothalamus in the metabolic regulation in the offspring of maternal obesity - Zhang, Jingyi; Li, Sujuan; Luo, Xiaoping; Zhang, Cai (Frontiers in Nutrition, 2023)
Maternal obesity has a great impact on the metabolism of offspring both in childhood and adulthood. Intrauterine metabolic programming is involved in the regulation of maternal obesity in offspring. However, the exact mechanisms remain unclear. Hypothalamus is the prime target organ of metabolic programming and the key regulatory center of energy metabolism. Increasing evidence has indicated the crucial role of hypothalamic regulation in the metabolism of offspring exposed to maternal obesity. This article reviews the development of hypothalamus, the hypothalamic regulations in energy homeostasis, possible mechanisms underlying the developmental programming of energy metabolism in offspring, and the potential therapeutic approaches to prevent metabolic diseases later in life. Lastly, we discuss about the difficulties and future aspects in the research of hypothalamic regulation in the metabolism of offspring born to obese mothers.